2008
DOI: 10.1080/15459620802656636
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Surface Lead Contamination, Hygiene Programs, and Work Practices of Bridge Surface Preparation and Painting Contractors

Abstract: A 2005 regulatory review of the lead in construction standard by the Occupational Safety and Health Administration (OSHA) noted that alternative pathways of exposure can be as significant as inhalation exposure and that noncompliance with the standard pertaining to hygiene facilities and practices was the second most commonly violated section of the standard. Noncompliance with provisions of the standard and unhealthy work and hygiene practices likely increase the likelihood of take-home lead via contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
1
15
1
Order By: Relevance
“…If this retrospective data is representative of the industrial painting industry, it is likely poor personal hygiene is contributing to the worker's lead body burden, which in turn may explain why elevated blood lead levels have remained constant in the target population. The results of this study support the findings of many other researchers who also found residual lead on workers' hands after handwashing at the conclusion of the workday[7] [8][11] [12]. Furthermore, the findings of this study support the need for improved work practice controls to manage lead exposures.These results have several associated limitations.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…If this retrospective data is representative of the industrial painting industry, it is likely poor personal hygiene is contributing to the worker's lead body burden, which in turn may explain why elevated blood lead levels have remained constant in the target population. The results of this study support the findings of many other researchers who also found residual lead on workers' hands after handwashing at the conclusion of the workday[7] [8][11] [12]. Furthermore, the findings of this study support the need for improved work practice controls to manage lead exposures.These results have several associated limitations.…”
supporting
confidence: 88%
“…Several studies have also provided evidence to support the proper use of PPE and basic personal hygiene practices in having a measurable impact upon the uptake of lead among workers [7] [9] [10]. There is also a growing body of evidence related to residual lead levels on the hands of workers after washing them at the conclusion of the workday [7] [8] [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Details of the sample collection and analysis are reported elsewhere. (18) Briefly, each worker was given two Wash ‘n Dri towelettes to wipe each hand for 30 sec. Hand wipes were collected during the midshift break and at the end of the work shift after workers had reportedly cleaned up.…”
Section: Methodsmentioning
confidence: 99%
“…Occupational exposure to inorganic lead is main features of this unusual case. Lead poisoning in adults primarily results from exposure by inhalation in the workplace [29]. We suspect that this patient suffered from lead poisoning from inhalation of fumes from car radiators and developed autonomic neuropathies which resulted in erectile dysfunction.…”
Section: Discussionmentioning
confidence: 92%